Indicators of time perception among students in special correctional and general education schools - Akhmetov S.M. ,; Aleksanyants G.D. ,; Medvedeva O.A. ,; Volkov A.V. ,; Selikhova E.G. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine indicators of time perception in 10-year-old children studying in correctional and general education schools. Methods and structure of the study. The examination involved 78 healthy primary schoolchildren (boys 10 years old) and 34 of their peers suffering from sensorineural hearing loss (III-IV degree). We used the computer program “Researcher of Temporal and Spatial Properties of Humans.” The “Individual Minute” (IM) test was used to reproduce the duration of the time interval. Results and conclusions. In healthy schoolchildren and in students with auditory deprivation, different numbers of children with a shortened IM, a long IM and a normal IM were noted. There are significant differences in the studied groups of children with shortened IM. No differences in indicators were recorded when reproducing the duration of a time interval with a light pulse.